Through the looking-glass - Carroll, Lewis (Penguin Classics; London, 2022)
"Step through the looking glass with Alice and discover the magic of Wonderland... This is the perfect introduction to Lewis Carroll's much-loved children's classic - Through the Looking Glass and What Alice Found There. Retold for a picture book audience, everyone's favourite characters are here, including Tweedledum and Tweedledee, Humpty Dumpty and the White Queen. With bouncy, rhyming text by award-winning author, Jeanne Willis, brought to life in vibrant colour by award-winning illustrator, Ross Collins."--Provided by publisher